An ıntegrated dematel – ıntuıtıonıstıc fuzzy topsıs methodology for logıstıcs centers locatıon selectıon - Uyanık, Cihan (My University, 2016)
BÜTÜNLEŞİK DEMATEL – SEZGİSEL BULANIK TOPSIS METODOLOJİSİ İLE LOJİSTİK MERKEZ YER SEÇİMİ 21. yüzyılda kentleşme küresel bir olgu halini aldı. Sanayinin kentlerde yoğunlaşması ve ona bağlı olarak kırsal alanın çözülmesiyle ticari faaliyetler ve nüfus yoğunluğu kentsel alanlarda toplandı. Kentleşmeyle ortaya çıkan ihtiyaçların ve kentleşmenin yarattığı sorunların doğrultusunda kentler yeniden yapılandırmaya devam ediyor. Sanayileşmeyle önemi her geçen gün artan lojistik sektörü de artan ticaret hacmini karşılamak için sürekli gelişim gösteriyor. Lojistik merkez konsepti de kentsel lojistiğin sorunlarına karşı üretilen çözümlerden biri olarak ortaya çıkmıştır. Kara, deniz, demiryolu, hava gibi taşımacılık türleriyle uyumlu, tüm taşımacılık faaliyetlerinin bir merkezde toplanmasıyla ekonomik, kent içi trafiğini ve çevre kirliliğini azaltmasıyla çevreci olması lojistik merkezleri etkili kılıyor. Gelişmekte olan ülkeler arasında yer alan, gelişmiş ülkelere göre kısıtlı kaynakları olan Türkiye için de lojistik merkezler kuşkusuz ki çok önemlidir. Bu çalışmada ise lojistik merkez kavramı, özellikleri, Avrupa’daki uygulamaları incelenmiş ardından lojistik merkez kurulum yeri problemleri üzerine yapılan çalışmaları içeren kapsamlı bir literatür taraması yapılmıştır. Literatür taraması yaygın kullanılan çözüm tekniklerini ortaya çıkarmış ve modelin çözümünde değerlendirilen kriterleri belirlemede kaynak olmuştur. Uygulamada İstanbul Metropolitan alanı ele alınmış Halkalı, Yeşilbayır (Hadımköy), Tuzla ve Çorlu olmak üzere 4 aday bölge belirlenmiştir. Çok Kriterli Karar Verme tekniklerinden DEMATEL ile kriterler arasındaki ilişki belirlenmiş ve etkisiz kriterler elenmiştir. Bir diğer Çok Kriterli Karar Verme tekniği Sezgisel Bulanık TOPSIS kullanılarak adaylar arasında sıralama yapılmış ve en uygun alternatif bulunmuştur. Lojistik Merkez, DEMATEL, Sezgisel Bulanık TOPSIS

AN INTEGRATED DEMATEL – INTUITIONISTIC FUZZY TOPSIS METHODOLOGY FOR LOGISTICS CENTERS LOCATION SELECTION In 21st. Century urbanization has become a global phenomenon. The fact that industrial activities concentrated on urban areas and after -because of the fact have mentioned- country-side diluted, commercial activities and population centered urban areas. In light of the needs and problems, which occurred as a result of urbanization, cities have been re-constructed; however, re-construction process have not finished yet. Logistics, which becomes more and more important with industrialization, is continuously developing to meet the needs of increasing volume. Therefore, concept of logistic center has emerged as one of the solution of urban logistics' needs and problems. What makes logistic centers effective is being economical by centralizing all transportation activities- which are compatible with transportation modes as land, sea, rail, air transportation- and is being environmentalist by reducing environmental pollution and traffic. As an economically growing country and as a country which has limited sources, there is no doubt that logistic centers are so important for Turkey. In this study, concept of logistics centers, its functions and implementations in Europe had been examined; after all, comprehensive literature review, which contains studies made on problematic of construction area of logistic center, made. Literature review picked out the common solutions and techniques. Moreover, it is helpful to determine which criteria are taken into consideration to solve the model. In implementation, area of Istanbul Metropolitan was handled; four candidates, which are Halkalı, Yeşilbayır (Hadımköy), Tuzla and Çorlu, are detected. By DEMATEL, one of the MCDM techniques, relationship between criteria are determined and ineffective criteria are eliminated. By using one of the other MCDM techniques, Intuitionistic Fuzzy TOPSIS, locations are ranked and most suitable alternative found. Logistics Centers, DEMATEL, Intuitionistic Fuzzy TOPSIS
Keywords: Endüstri, Mühendislik